Collision of emotional intelligence and work centrality on work-life balance - a supportive work environment for working professionals. (3rd October 2019) - Susi, S.; Jothikumar, R.; Suresh, A.
This study examined the differences among working professionals of nurses at varied levels of emotional intelligence and work centrality on work-life balance and its dimensions. One-way ANOVA was the statistical tools applied in this research for analysis. Analysis demonstrated that, significant differences were found between working professionals of nurses with low, average and high emotional intelligence and work centrality on the dimensions of work interference with personal life, personal life interference with work, work personal life enhancement and work life balance.